Mechanical Characterization of Lightweight Foamed Concrete - Marcin Kozłowski; Marta Kadela (Advances in Materials Science and Engineering)
Foamed concrete shows excellent physical characteristics such as low self weight, relatively high strength and superb thermal and acoustic insulation properties. It allows for minimal consumption of aggregate, and by replacement of a part of cement by fly ash, it contributes to the waste utilization principles. For many years, the application of foamed concrete has been limited to backfill of retaining walls, insulation of foundations and roof tiles sound insulation. However, during the last few years, foamed concrete has become a promising material for structural purposes. A series of tests was carried out to examine mechanical properties of foamed concrete mixes without fly ash and with fly ash content. In addition, the influence of 25 cycles of freezing and thawing on the compressive strength was investigated. The apparent density of hardened foamed concrete is strongly correlated with the foam content in the mix. An increase of the density of foamed concrete results in a decrease of flexural strength. For the same densities, the compressive strength obtained for mixes containing fly ash is approximately 20% lower in comparison to the specimens without fly ash. Specimens subjected to 25 freeze-thaw cycles show approximately 15% lower compressive strengths compared to the untreated specimens.